Emotional Freedom Tehcniques and Psychological Response of Mother Post Partum Survivor Covid 19 - Simbolon, Ganda Agustina Hartati; Sitohang, Tiur Romatua (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
As a long-term psychological consequence, postpartum mothers who survive COVID-19 may have psychological symptoms such as increased stress, uncertainty, sorrow, worry, and depression. Several studies have shown elevated levels of stress, anxiety, and depressed symptoms, including suicidal ideation, in pregnant and postpartum women throughout the globe during the COVID-19 pandemic. In a similar research, EFT counseling resulted in a substantial reduction in anxiety and depression ratings among COVID-19-positive participants. The purpose of this research was to compare the psychological reactions (depression, anxiety, and stress) of postpartum moms proclaimed healed of COVID-19 before and after receiving emotional liberation methods treatment in the intervention group vs the control group. "Quasi-Experimental Pre-Post Test with a Control Group" 15 respondents were assigned to the intervention group and 15 to the control group. Asymp sig (2-tailed) of 0.05 was achieved. Thus, EFT has an impact on the psychological reactions of postpartum women who have survived COVID 19. It is anticipated that health care professionals would use EFT to the treatment of pregnant, maternity, and postpartum women in order to lessen the negative reactions that mothers often feel throughout these stages. in addition to non-pharmaceutical alternatives.